32.0k views
1 vote
Evaluate the expression below for x = 2, y = –3, and z = –1.

A.

–23

B.

–5

C.

13

D.

27

1 Answer

5 votes

Correct question:

Evaluate the expression below for x = 2, y = –3, and z = –1.

Given:
x^2 z^2 -y^2(x+z)

Options:

A.–23

B.–5

C.13

D.27

Answer:

B. -5

Explanation:

In this question we are given the following values:

x = 2

y = -3

z = -1

Given the expression:


x^2 z^2 -y^2(x+z)

To evaluate, let's substitute for 2, -3 & - 1 for x, y & z respectively

Therefore,


x^2 z^2 -y^2(x+z)

Substituting values, we have:


(2^2) (-1^2) - (-3^2)(2+(-1))

Simplifying, we have:


[(2^2) (-1^2)] - [(-3^2)(2-1)]


= [(4) (1)] - [(9)(1)]


= 4 - 9

= -5

The correct answer is option B

User SlugFiller
by
5.5k points